Revisiting agency theory in franchising law in Malaysia - Mohd Ishan, Zahira; Abdullah, Farhan (TextRoad Publication, 2015)
Franchising being developed from a hybrid body of laws including agency. Applying the qualitative approach by means of inductive reasoning, this article aims at exploring the limits of agency theory in relation to franchising in Malaysia by the method of historical approach. The elements of franchisors' controls, often lead to the debates of whether franchisors are principals to their franchisees and whether their relationship is fiduciary in nature or at an arm's length. The former issue is common in a third party claim on franchisor's liability over the act done by his franchisee. The latter issue is common in the day-today relationship of the franchisor and his franchisees. On September 20, 2012, the Malaysian Parliament amended the Malaysian Franchise Act 1998 (effective 1st January 2013) which has gone through a number of changes, some of them notable. With statutory intervention, the finding shows that the agency theory may have a very limited role in the national franchise industry.